Seaweed Sulfated Polysaccharides against Respiratory Viral Infections - Mehwish Jabeen; Mélody Dutot; Roxane Fagon; Bernard Verrier; Claire Monge (MDPI AG, 2021)
Respiratory viral infections have been a leading cause of morbidity and mortality worldwide. Despite massive advancements in the virology field, no specific treatment exists for most respiratory viral infections. Approved therapies against respiratory viruses rely almost exclusively on synthetic drugs that have potential side effects, restricting their use. This review aims to present natural marine sulfated polysaccharides possessing promising antiviral activity against respiratory viruses that could be a safe alternative to synthetic broad-spectrum antiviral drugs. The antiviral properties of marine sulfated polysaccharides are presented according to their mechanism of action on different types and strains of respiratory viruses, and the potential limits of their use are discussed.